Organocatalysis for the Acid‐Free O‐Arylidenation of Carbohydrates. Issue 31 (2nd October 2013) - Geng, Yiqun; Faidallah, Hassan M.; Albar, Hassan A.; Mhkalid, Ibrahim A.; Schmidt, Richard R.
Abstract: Methyl glycopyranosides of glucose, galactose, and mannose, their 2, 3‐di‐ O ‐benzyl‐protected derivatives, as well as the unprotected sugars react with p ‐methoxybenzaldehyde dimethyl acetal (3 ) and with benzaldehyde dimethyl acetal (7 ) as reagents in the presence of thiourea1 or squaramide2 as the organocatalyst to afford regioselectively 4, 6‐ O ‐arylidenated derivatives5 and8 . With an excess amount of3 or7, diarylidenated derivatives are also obtained. In situ formation of acetals of type3 and7 from corresponding aldehydes10 and13 in the presence of an orthoester and organocatalyst1 or2 can be used to generate5 and8 directly from the aldehydes. Some substrates also lead to mixed orthoesters with this procedure. The reaction courses are discussed. Abstract : A squaramide catalyzes the 4, 6‐ O ‐arylidenation of glucose, mannose, and galactose with the use of arenecarbaldehyde dimethyl acetals or arenecarbaldehydes and orthoesters as the reagents. Glycoside derivatives also undergo this reaction.